Specific cellular immune response and neutralizing antibodies in goats immunized with native or recombinant envelope proteins derived from human T-lymphotropic virus type IIIB and in human immunodeficiency virus-infected men. - Krohn, K (1987)
Animals immunized with native or recombinant envelope proteins from the human immunodeficiency virus (HIV, formerly referred to as human T-lymphotropic virus type III) human T-lymphotropic virus type IIIB and naturally HIV-infected men were assessed for neutralizing antibodies and cell-mediated immunity toward the virus. Immunization of rabbits or goats with the native external envelope glycoprotein gp120 or with corresponding recombinant proteins elicited strictly type-specific neutralizing antibodies. A broad, group-specific cellular immune response to gp120 and to three different HIV isolates was seen in goats immunized with the native gp120 but not in animals immunized with the nonglycosylated recombinant envelope proteins. In HIV-infected people, no T-cell response was seen, even though their T-cell response toward other foreign antigens was intact. The results show type- and group-specific epitopes on gp120, some of which may be of importance for the development of a vaccine against HIV infection.